Significations et interprétations de la gravité des événements violents : le cas des voies de fait traitées à la Cour municipale de Montréal - Nonn, Éva (Criminologie, 1991)
Based on the results of an empirical study on the judicial treatment of cases of assault and battery at the Municipal Court of Montreal, this article focuses on one particular aspect of this treatment, the classification of certain acts as infractions. Its object is to describe and analyze the socio-political and juridic factors that can influence the decisions made by the police and prosecutors when pronouncing the charges. By comparing these charges with the legal and extra-legal variables, we see a difference in the classification of similar cases depending on the family or social context. This supposes some difficulty in defining the criminal gravity of acts committed in conflicts involving parties bound by other bonds as well as their case before the court.